COVID-19 severity prediction in patients with chronic hepatitis C depending on the liver fibrosis stage - E. N. Temnik; D. Yu. Konstantinov; L. L. Popova; N. P. Persteneva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
The aim of the study was to develop a method for assessing the risk of severity of the novel coronavirus infection COVID-19 in patients with chronic hepatitis C depending on the severity of liver fibrosis.Object and methods. The results of laboratory data of patients with COVID-19 and chronic hepatitis C (n = 147) were analyzed. According to the severity of liver fibrosis, patients with COVID-19 with chronic hepatitis C were divided into 3 subgroups: mild fibrosis (F1), moderate fibrosis (F2), severe fibrosis (F3). In blood serum, the parameters of total and biochemical (C-reactive protein, lactate dehydrogenase, alanine aminotransferase, aspartate aminotransferase, gamma-glutamyl transpeptidase, gamma-globulins, ferritin) blood tests, lipid profile (high-density lipoprotein cholesterol, triglycerides, apolipoprotein A1, apolipoprotein B), hemostasis (fibrinogen, activated partial thromboplastin time), cytokines (interleukin-2, tumor necrosis factor-а). All parameters were assessed in the acute period, depending on the severity of COVID-19 and the stage of liver fibrosis.Outcomes. Computer program for predicting the severity of COVID-19 in patients with chronic hepatitis C, depending on the stage of liver fibrosis, can be introduced into clinical practice for managing patients in the certain group.